2007
DOI: 10.1002/app.27027
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity of boron nitride epoxy‐matrix composite through multi‐modal particle size mixing

Abstract: Castable particulate-filled epoxy resins exhibiting excellent thermal conductivity have been prepared using hexagonal boron nitride (hBN) and cubic boron nitride (cBN) as fillers. The thermal conductivity of boron nitride filled epoxy matrix composites was enhanced up to 217% through silane surface treatment of fillers and multi-modal particle size mixing (two different hBN particle sizes and one cBN particle size) prior to fabricating the composite. The measurements and interpretation of the curing kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
191
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(197 citation statements)
references
References 26 publications
4
191
0
2
Order By: Relevance
“…Most polymers have a thermal conductivity between 0.1 and 0.6 W m −1 K −1 [1]. In order to improve the thermal conductivity of polymers, inorganic fillers with a higher thermal conductivity than the host, such as aluminium nitride (AlN) [2][3][4][5][6][7][8], boron nitride (BN) [3,4,6,[9][10][11][12], aluminium oxide (Al 2 O 3 ) [4,10,13,14], silicon dioxide (SiO 2 ) [4,15,16], silicon carbide (SiC) [10,13], silicon nitride (Si 3 N 4 ) [10,15,17], carbon nanotubes [18,19] and nanodiamond [15,16], are used to create polymer-based composites with improved thermal conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Most polymers have a thermal conductivity between 0.1 and 0.6 W m −1 K −1 [1]. In order to improve the thermal conductivity of polymers, inorganic fillers with a higher thermal conductivity than the host, such as aluminium nitride (AlN) [2][3][4][5][6][7][8], boron nitride (BN) [3,4,6,[9][10][11][12], aluminium oxide (Al 2 O 3 ) [4,10,13,14], silicon dioxide (SiO 2 ) [4,15,16], silicon carbide (SiC) [10,13], silicon nitride (Si 3 N 4 ) [10,15,17], carbon nanotubes [18,19] and nanodiamond [15,16], are used to create polymer-based composites with improved thermal conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Several polymer composites using aluminum nitride (AlN) [4] and boron nitride (BN) [5] powders (or fillers) were fabricated and their performance was tested. Some important physical properties, including the purity and the size, are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…A significant amount of research works was found where particulate filler materials were introduced in polymer to increase its effective thermal conductivity (Agrawal et al, 2000;Boudenne et al, 2004;Miller et al, 2006;Mu, Feng and Diao, 2007;Subodh et al, 2008;Vinod, Varghese and Kuriakose, 2004;Sundstrom and Chen, 1970;Kim et al, 2008;Pal, 2007). The equivalent thermal conductivity (ETC) of particulate filled polymer composites was also investigated with the variation of various morphological properties of conductive filler particles (Ye, Shentu and Weng, 2006), multi-modal particle size mixing (Yung and Liem, 2007) as well as using hybrid filler materials (Lee et al, 2006). Moreover, addition of filler particles in mould material increases the effective modulus of elasticity of mould materials (Tavman, 1997;Rusu, Sofian and Rusu, 2001;Papanicolaou and Bakos, 1992).…”
Section: Introductionmentioning
confidence: 99%